Warmer Environments Increase Implicit Mental Workload Even If Learning Efficiency Is Enhanced - Kimura, Tsukasa; Takemura, Noriko; Nakashima, Yuta; Kobori, Hirokazu; Nagahara, Hajime; Numao, Masayuki; Shinohara, Kazumitsu (Frontiers in Psychology, 2020)
Climate change is one of the most important issues for humanity. To defuse this problem, it is considered necessary to improve energy efficiency, make energy sources cleaner, and reduce energy consumption in urban areas. The Japanese government has recommended an air conditioner setting of 28 ℃ in summer and 20 ℃ in winter since 2005. The aim of this setting is to save energy by keeping room temperatures constant. However, it is unclear whether this is an appropriate temperature for workers and students. This study examined whether thermal environments influence task performance over time. To examine whether the relationship between task performance and thermal environments influences the psychological states of participants, we recorded their subjective rating of mental workload along with their working memory score, electroencephalogram (EEG), heart rate variability (HRV), skin conductance level (SCL), and tympanum temperature during the task and compared the results among different conditions. In this experiment, participants were asked to read some texts and answer questions related to those texts. Room temperature (18, 22, 25 or 29 ℃) and humidity (50%) were manipulated during the task and participants performed the task at these temperatures. The results of this study showed that the temporal cost of task and theta power of EEG, which is an index for concentration, decreased over time. However, subjective mental workload increased with time. Moreover, the low frequency to high frequency ratio (LF/HF) and SCL increased with time and heat (25 and 29 ℃). These results suggest that mental workload, especially implicit mental workload, increases in warmer environments, even if learning efficiency is facilitated. This study indicates integrated evidence for relationships among task performance, psychological state and thermal environment by analyzing behavioral, subjective, and physiological indexes multidirectionally.